Physical characteristics of different professional rugby union competition levels - Tierney, P.; Blake, C.; Delahunt, E. (Journal of Science and Medicine in Sport, 2021)
Objectives: To evaluate whether differences in physical characteristics (running-related and collision-related metrics) exist between four different professional rugby union competition levels. Design: We collected and retrospectively analysed microsensor technology data from players of two professional rugby union clubs that competed across four different competition levels: International rugby union, European Rugby Champions Cup, PRO14 club competition, and British and Irish Cup. Methods: Differences between competition levels were analysed using a one-way ANOVA test. The Tukey HSD test was completed to perform multiple pairwise-comparisons between the means of the competition levels and player positional groups. Results: Ten of the 12 microsensor technology derived physical characteristics were significantly different between competition levels. Collision load-, collisions-, and high metabolic load efforts-per minute all increased at higher competition levels. These differences were also noted across player positional groups. Conclusions: The physical characteristics of rugby union match-play differ across competitions levels. Our data suggest that professional rugby union players require specific physical preparation for different competition levels. In particular, players are likely to need specific preparation and recovery for the higher collision intensity observed at higher competition levels.